Explorations of the Role of Digital Technology in HIV-Related Implementation Research: Case Comparisons of Five Ending the HIV Epidemic Supplement Awards. (1st July 2022) - Jones, Jeb; Knox, Justin; Meanley, Steven; Yang, Cui; Lounsbury, David W.; Huang, Terry T.; Bauermeister, Jose; Gonzalez-Hernandez, Graciela; Frye, Victoria; Grov, Christian; Patel, Viraj; Baral, Stefan D.; et al.
Abstract : Introduction: The use of digital technology in HIV-related interventions and implementation strategies is increasing. Whether the use of technology is to directly improve patient outcomes (ie, part of the intervention) or as part of the strategy to implement interventions has important implications. In this article, we present 5 case studies of projects that feature the use of technology in HIV-related implementation research to identify and describe challenges specific to technology-based implementation research about study design, outcome measurement, implementing in an evolving technology landscape, and equity. Methods: For each case study, we identified the technological components, classified the components as intervention or implementation strategy, and identified implications for measuring performance and ensuring equity. The Exploration, Preparation, Implementation, and Sustainment framework was used to identify the research stage of each project. Results: Technology is being leveraged across a diverse array of implementation strategies to promote Ending the HIV Epidemic in the United States. The case studies were primarily in the exploration and preparation phases of implementation, yet technology played a different role in each project— developing educational materials, mass media to recruit participants or distribute evidence-based campaigns, providing training, guiding tailoring, and implementing novel methods to democratize intervention development. Discussion: Technology can play multiple roles in HIV-related implementation research projects, including serving as the intervention, being leveraged within implementation strategies, or both. We identified multiple considerations across projects that should be taken into account when measuring success and planning for equitable and sustained impact.